Examining Mula Jadi Na Bolon in the Traditional Belief of Toba Batak People - Sitanggang, Pintor Marihot (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2023)
Abstract: This article describes the traditional Batak’s belief in the era of pre-christian mission to the Batak people in North Sumatera, Indonesia. The traditional Batak’s belief the mythology of Mula Jadi Na Bolon, was believed as ultimate and absolute power, the creator of the world and everything inside the world. The Batak people worshiped Mula Jadi Na Bolon, offered offering and had ritual worshiping Mula Jadi Na Bolon. They called Mula Jadi Na Bolon as Debata, then this the word that I.L. Nommensen used to translate God as Debata in Batak’s language. When the Christian Missionaries arrived among the Toba Batak people, they found the Toba Batak people to be a devoutly zealous people with the vivid awareness of religious power in the world around the Toba Batak people. While many of these religious notions were condemned by missionaries, Batak piety toward the dynamic activity of religious power was preserved in a Christian context. By using the qualitative research method, this article describes the theological approach acknowledging the traditional Batak’s belief in Mula Jadi Na Bolon as High God. This article explores the Christian Mission approaching to the Batak people, how the missionary used the inculturation in Christian Mission’s method to approach the Batak people. This research describes how the Batak people shifted from the traditional belief to the Christian teaching. Keywords: Mula Jadi Na Bolon, Batak people, Mythology, Christian, Mission.